Predictive value of microRNA-132 and its target gene NAG-1 in evaluating therapeutic efficacy of non-steroidal anti-inflammatory drugs treatment in patients with ankylosing spondylitis - Guo, Tuan-Mao; Yan, Yong; Cao, Wei-Ning; Liu, Qiang; Zhu, Hai-Yun; Yang, Lan; Gao, Mai-Cang; Xing, Yan-Li (Clinical rheumatology, 2018)
Ankylosing spondylitis (AS) is a common chronic rheumatic disorder, accompanied by the differential expression of various microRNAs (miRNAs) in patients suffering from the condition, some of which have the potential to serve as novel complementary AS biomarkers. During this study, AS patients were recruited in connection with our investigation into the correlation of microRNA-132 (miR-132) in peripheral blood and its target gene NAG-1 expressions in relation with the clinical efficacy of non-steroidal anti-inflammatory drugs (NSAIDs) treatment in patients with AS. A total of 218 AS patients who had been previously treated with oral diclofenac sodium and were placed into either the response ( n = 175) or non-response groups ( n = 43) following a 16-week period of therapeutic evaluation. An additional 113 healthy patients were also recruited for the purposes of the study. AS patient peripheral blood samples were obtained at the 0th, 8th, and 16th week, with the corresponding samples of the healthy patients collected at week 0. The expressions of miR-132 and NAG-1 were detected by RT-qPCR and analyzed using a ROC curve for the elucidation of the diagnostic value of peripheral blood miR-132 expressions as well as their predictive value among AS patients undergoing NSAIDs treatment. The targeting relations of miR-132 and NAG-1 were validated by microRNA.org and luciferase assay. Greater levels of peripheral blood miR-132 expression were observed among AS patients prior to treatment, in comparison to the healthy patients in the study. Prior to treatment, the area under the miR-132 ROC curve (AUC) of AS patients was 0.965, with a critical point of 2.605. The sensitivity and specificity of miR-132 were 91.7 and 97.3%, respectively, in regard to the AS diagnostic clinical efficacy. In comparison with the non-response group, the miR-132 expression of patients in the response group exhibited descended levels while the mRNA expression of NAG-1 increased. The ROC results indicated that the AUC of miR-132 was 0.876 with its sensitivity and specificity observed to be 95.3 and 80.0%, respectively. The AUC of NAG-1 was 0.912 with its sensitivity and specificity observed to be 76.6 and 79.1%, respectively. In comparison with the high miR-132 expression group and the low NAG-1 mRNA expression group, significantly improved blood biochemistry indexes, sign indexes, blood indexes, and adverse reaction rate were observed among the low miR-132 expression group and the high NAG-1 mRNA expression group. The microRNA.org and luciferase assay revealed NAG-1 to be a target of miR-132. Based on the results of this study, it was concluded that the expressions of MiR-132 and NAG-1 could serve as biological markers in the prediction of the therapeutic efficiency of NSAID treatment in AS patients.